Resource mobilization for sustainable management : proceedings of a Workshop on Major Irrigation Schemes in Sri Lanka, held at Kandy, Sri Lanka, 22-24 February, 1990 - International Irrigation Management Institute .; Workshop on Major Irrigation Schemes in Sri Lanka (1990 : Kandy, Sri Lanka); International Irrigation Management Institute (Colombo : International Irrigation Management Institute, 1990)
Contributed papers.
Includes bibliographical references.
Keywords: Irrigation -- Sri Lanka -- Management -- Congresses